Islamic college libraries facing the covid-19 pandemic: Study at IAIN Curup’s Library - Rhoni Rodin (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2022)
Background of the study: The library has been running normally. But it changed 360 degrees when the COVID-19 pandemic outbreak hit. Purpose: The purpose of this study was to analyze how Islamic university libraries in Indonesia faced the COVID-19 pandemic, especially the IAIN Curup Library. Method: The design of this research is descriptive qualitative, the informants in this study are the head of the library and management staff / librarian, and the data collection technique uses surveys, interviews and documentation. While the data analysis using qualitative descriptive techniques. Findings: The results of the study show that there are several creativity and innovations that have been carried out by the IAIN Curup Library in dealing with the current epidemic of the Covid-19 pandemic, including 1) Making online membership cards; 2) SKBP services online; 3) Access books online; 4) Join to telegram; and 5) Auto WhatsApp as an alternative to library services. Then there are several things that the IAIN Curup library has done in the face of the covid 19 pandemic, namely 1) strengthening e-resources at IAIN Curup such as e-repository, IAIN Curup e-library, e-theses, and open educational resources, where all these resources will support lectures and other academic activities. 2) Implementation of health protocols when entering the library, for example wearing masks, maintaining distance, limiting the number of visitors, and providing good sanitation facilities. Conclusion: The Covid 19 pandemic that is currently engulfing the library has closed all doors for visitors so that the library has no visitors at all (in this case a physical visit) to the library, therefore facing this issue, the Islamic CollegeLibrary in this case must do the following: creativity and innovation.